Socrates in the Clouds: Excess and Impiety - Cruickshank, Peter (My University, 2008)
This paper seeks to analyse the portrayal of Socrates in the Clouds in detail, with emphasis on the particularly unflattering aspects of the depiction, aspects which may have soured the public's perception of Socrates, or else at least may vocalize an already-soured perception of him. The establishment of the exact nature of this depiction is the primary objective of this paper then. But an interesting theme will emerge: the negative qualities in the depiction of Socrates will be shown to have a unity, rather than being random jabs. They constitute a general stereotype of the intellectual of the time, and the underlying criticism behind all of the negative qualities is that the intellectual is perceived to reject the middling egalitarian values so essential to his state. A large part of this rejection will be his religious heterodoxy, and the important implications that has for his character. The study of the nature of the portrayal of Socrates in the Clouds is a worthwhile topic by itself, but this detailed analysis of the depiction will also provide a useful point of reference for further studies of Aristophanes' comedy, Socrates' trial, and fifth and fourth century Athenian attitudes towards intellectuals.
Keywords: Classics; Classics